Amelioration of ochratoxin-A induced cytotoxicity by prophylactic treatment of N-Acetyl-L-Tryptophan in human embryonic kidney cells. (15th January 2020) - Agarwal, Prerna; Singh, Darshana; Raisuddin, Sheikh; Kumar, Raj
Graphical abstract: Highlights: Ochratoxin A induced oxidative stress reduction by N -Acetyl-L-Tryptophan. Protein synthesis inhibition by OTA by interaction with phenylalanyl t-RNA synthetase and its protection by N -Acetyl-L-Tryptophan. Mitochondrial membrane de-stabilization by Ochratoxin A and restoration by N -Acetyl-L-Tryptophan. Protection from Ochratoxin A induced cell death by N -Acetyl-L-Tryptophan. Abstract: Ochratoxin A (OTA) is known to induce nephro-toxicity via induction of cellular redox homeostasis perturbation, mitochondrial hyperpolarisation and depolarization, protein synthesis inhibition leading to apoptosis. In the present study, protective efficacy of N -Acetyl-L-Tryptophan (NAT) against OTA induced toxicity was evaluated using Human Embryonic Kidney (HEK-293) cells. Cells were treated with NAT (0–200 μg/ml) before OTA treatment (0–20 μg/ml) and protective efficacy of NAT was evaluated using MTT and SRB assay. OTA-induced intracellular ROS generation and its inhibition by NAT (2.5 μg/ml) pre-treatment was evaluated using 2′, 7′-dichlorodihydrofluorescein diacetate (H2 DCFDA) probe. Effects of NAT pre-treatment on OTA treated cells were also evaluated in terms of cell cycle perturbations and mitochondrial membrane potential disturbance using flowcytometry. Results of the study demonstrated significant (∼89 % cell growth in comparison to 50% in OTA alone group; P < 0.05) protection by NAT to the HEK-293 cells against OTA mediated cell death in terms of cell viability. Further, significant reduction in ROS levels and mitochondrial membrane potential disturbance was also observed in NAT pre-treated plus OTA cells as compared to only OTA treated cells. Significant (p < 0.05) arrest in G0 and S phase of cell cycle was observed in OTA treated cells that was found to be inhibited by NAT pre-treatment to OTA treated cells. Also, molecular docking analysis demonstrated higher probability of NAT to bind with OTA binding pocket on phenylalanyl t-RNA synthetase, resulting in inhibition of OTA incorporation in the newly synthesized peptides and thus may ameliorate OTA induced protein synthesis inhibition. Conclusively, present study suggested that NAT offers protection against OTA toxicity in HEK-293 cells by counterbalancing oxidative stress, cell cycle regulation, mitochondrial membrane potential stabilization, protein synthesis inhibition and cell death retardation.